OPTIMIZATION OF THE IMPLEMENTATION OF AUTOMATIC EXCHANGE OF INFORMATION (AEOI) IN BOOSTING STATE REVENUE ON INCOME TAX LEVELS: OPTIMALISASI PENERAPAN AUTOMATIC EXCHANGE OF INFORMATION (AEOI) DALAM MENDORONG PENDAPATAN NEGARA ATAS PUNGUTAN PAJAK PENGHASILAN - Dini Vientiany; Mulia Syahputri; Amanda Mutiara; Siti Nurhalimah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to evaluate the optimization of the implementation of AEOI in boosting state revenue through income tax. The hope of this research is to find an effective solution to overcome the costs and complexities faced in implementing AEOI, so that it can increase state revenue through income tax. This research uses qualitative research methods with a focus on document analysis (library research) to evaluate the optimization of the application of Automatic Exchange of Information (AEOI) in increasing state revenue through income tax in Indonesia. Overall, AEOI has proven to be an effective instrument in increasing state revenues from income tax by expanding the tax base and increasing taxpayer compliance. However, to maximize its potential, continued efforts are needed from the government to increase taxpayer understanding, strengthen DGT resources, and increase cross-institutional collaboration.